Explorations in the theory of language - Seuren, Pieter A. M (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; Introduction -- 1. The settling of a language -- 2. The Whorf hypothesis -- 3. Relativism or a universal theory? -- 4. What does language have to do with logic and mathematics? -- 5. A test bed for grammatical theories -- 6. The Chomsky hierarchy in perpsective -- 7. Reflexivity and identity in language and cognition -- 8. The generalized logic hierarchy and its cognitive implications -- 9. The intensionalization of extensions